Ruth Crawford Seeger : a composer's search for American music - Tick, Judith (Oxford University Press, 2000)
Ruth Crawford Seeger (1901-1953) is frequently considered the most significant American female composer in this century. Joining Aaron Copland and Henry Cowell as a key member of the 1920s musical avant-garde, she went on to study with modernist theorist and future husband Charles Seeger, writing her masterpiece, String Quartet 1931, not long after. But her legacy extends far beyond the cutting edge of modern music. Collaborating with poet Carl Sandburg on folk song arrangements in the twenties, and with the famous folk-song collectors John and Alan Lomax in the 1930s, she emerged as a central.